Model Pengabdian Masyarakat Berbasis Kawasan - Fakhruddin Fakhruddin (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Research problems increase community empowerment through the process of human capital and physical capital in the area around the community. The research objective is to develop a model that is supported by the concept of theoretical development. This research focuses on